Pengaruh Ion Logam Co2+ dan Cu2+ Pada Proses Fotodegradasi Direct Blue 3R Menggunakan Fotokatalis Komposit ZnO-Karbon Aktif - Wicaksono, Aji Putro (Chem Info Journal, 2013)
Been conducted synthesis and characterization of ZnO-activated carbon composites, and examines the impact of the presence of metal ions Co2+ and Cu2+ in the process of photodegradation Direct Blue 3R and photoreduction metal ions. Synthesis of ZnO with the XRD results obtained ZnO (wurzite) D = 27.97 nm; Eg = 3.8 eV. Composite ZnO-activated carbon produced in tablet form with d = 0.8 cm; t = 0.45 cm gray. SEM and BET characterization of the resulting composite has a hollow morphology with a surface area ZnO-carbon composite activated by 27.209 m2/g, pore volume of 0.089 cc/g; finger pores of 3.25 nm and has a high effectiveness in the photodegradation of dye Direct Blue 3R of 95.36%. The optimum pH for photodegradation process is at pH 4 with the effectiveness of 91.92%. The addition of metal ions Co2+ and Cu2+ can increase the effectiveness of photodegradation Direct Blue 3R and can simultaneously reduce metal ions Co2+ and Cu2+ into Co(s) and Cu (s) with the optimum concentration of each metal is 12 ppm. The optimum time for photodegradation process is 2 hours. Photodegradation effectiveness of 94.875% and 76.31% on the addition photoreduction Co2+, whereas the addition of Cu2+ photodegradation effectiveness of 96.208% and 89.33% photoreduction.